HISTORIOGRAPHY OF THE ETHNOGRAPHY OF THE OASIS OF SOUTHERN UZBEKISTAN - Iskandarov Sherzod Abduganievich (Western European Studies, 2025)
As a result of the research carried out on the basis of field studies mateirallar on the basis of research I have tried. The ethnology of uzbekistan kashkadarya region population ethnic identity in the twentieth century virtually nonexistent in the literature to realize the specialis. Man ancient oral literature of the peoples of central asia and among the people is the creation of na'muna, "Alpomish",1 abu rayhan biruni scholars as well as popular entsiklopedist, great scientists science the time, Ahmad Yassaviy, Narshaxiy, statesman and poet of zahiriddin babur historical-artistic works are of particular significance.2Also, some of the seeds in the oasis at work, however, ethnic history, Muhammad Salih about to settle down and come to oasis "Shayboniynoma", ("Sharafnomayi the king"), a abulg'ozi "shajarai a turkey" as the game was used.3 This source is important for the research and literature, history and ethnography of uzbekistan on December ethnic in this game there is valuable information
Keywords: Shayboniynoma; zahiriddin; game; entsiklopedist